Experimental justification efficiency of use of technical devices in improving methods of arrest offenders - Oleg Yareshenko (Слобожанський науково-спортивний вісник, 2014)
Purpose: to enhance the quality of education through the introduction of detention receptions in the training process of personnel Ministery of Internal Affairs technical devices urgent information. Material and Methods: the study involved 60 third-year cadets of Kharkiv National University of Internal Affairs. Were used: a theoretical analysis of the literature; method of expert evaluations; teacher testing and pedagogical experiment. Results: it was found that the use in the course of special training funds urgent information significantly improves the quality of cadets mastering the techniques of detention. Conclusions: the use of the training of personnel Armed Forces of Ukraine means urgent information is promising and warrants further continuation.